Health insurance status and hearing aid utilization in U.S. older adults: A population-based cross-sectional study - Kaitlin Hori; Albert Li; Diego E. Razura; John Parsons; Janet S. Choi (PLoS ONE, 2026)
Background The role of health insurance and its diverse hearing health benefits on hearing aid utilization is currently unknown. The objective of this study is to examine rates of ever and regular hearing aid (HA) use by insurance status in older U.S. adults. Methods This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) (2005–2018). Older adults (≥65 years) with complete data on health insurance, audiometry, and hearing aid use (n = 3,172) were included. Eight combinatorial insurance categories were created and compared pairwise to the reference of Medicare only coverage. Outcomes included ever and regular hearing aid use. Results Among older U.S. adults, 30.3% [95% CI:27.6%−33.2%] of those with audiometry-measured hearing loss reported ever using HAs while 22.9% [95% CI:20.3%−25.7%] reported regular HA use. Among older adults with hearing loss, those with military-related insurance (Tricare, VA and Champ-VA) had amongst the highest rates of ever and regular HA use (43.3% [95% CI:31.3%−56.2%] and 30.8% [95% CI:21.1%−42.5%], respectively). Ever HA use rates for individuals with Medicare and Medicaid was 30.8% [95% CI:27.8%−33.8%] and 17.7% [95% CI:11.9%−25.5%], respectively. In a multivariable model adjusting for demographics and hearing loss severity, individuals with military-related and military-related+Medicaid insurance were significantly more likely to report ever using HAs compared to those with Medicare only (OR 1.80, 95% CI:1.03–3.16; OR 20.38, 95% CI:1.07–386.84, respectively). Those with military-related insurance were more likely to report regular HA use (OR 2.17, 95% CI:1.16–4.09). Conclusion In this nationally representative study of older U.S. adults, we found differences in ever and regular HA use rates by insurance status, even when adjusting for hearing loss, demographics, and comorbidities. Future research is warranted to investigate group-specific differences, including access to hearing care, hearing health benefits, and stigma, to better understand the facilitators and barriers to hearing aid use by insurance status.